TERAPI ENDOVASKULAR ANEURISMA KAROTIS KAVERNOSA DENGAN PIPELINE FLEX EMBOLIZATION DEVICE: PENGAMATAN 1 TAHUN - Muhammad Yunus Amran; Seung Pil Ban; Ashari Bahar; O-Ki Kwon (PERDOSNI, 2019)
ENDOVASCULAR TREATMENT CAVERNOUS CAROTID ANEURYSM WITH PIPELINE FLEX EMBOLIZATION DEVICE: 1-YEAR FOLLOW UPABSTRACTAsymptomatic intracranial aneurysms are usually detected accidentally through neuroimaging. However, a large intracranial aneurysm (15-24mm) is more likely to manifest clinically due to its mass effect. Aneurysms in the cavernous segment of carotid artery generally exhibit occulomotor nerve palsy, headache and dizziness. The selection of endovascular therapy depends on the type and morphology of the aneurysm. Currently, the treatment options were stent-assisted coil and pipeline embolization device (PED). We reported two cases of large symptomatic unruptured cavernous carotid aneurysm (CCA), treated with the flow diverter technique using a pipeline flex embolization device (PED flex) the second generation of PED. The first case was a 59-year-old woman with complaint of diplopia and headache. Computed Tomography (CT) angiography and 3 dimensional (D) brain imaging revealed bilateral aneurysms, one was in the right cavernous carotid (16.1x16.6mm) and the other was in the left cavernous carotid (9.2x6.5mm). In second case a 67-year-old woman with complaint of headache. Magnetic resonance angiography (MRA) revealed a 15mm aneurysm in the right cavernous carotid. Both aneurysms were treated using PED flex (4.75mm diameter/25mm length and 4mm diameter/25mm length, respectively), except the left cavernous carotid aneurysm in the first case. Six month and one year follow up angiograms were obtained, and showed complete occlusion of aneurysms. Flow diverter technique using PED flex is a feasible and effective treatment for large symptomatic unruptured carotid cavernous aneurysms.Keywords: Embolization, flow-diverter, large cavernous carotid aneurysms, pipeline flex embolization device (PED flex)ABSTRAKAneurisma intrakranial asimptomatik biasanya terdeteksi secara tidak sengaja melalui pemeriksaan pencitraan neuroradiologis. Akan tetapi aneurisma intrakranial yang besar (15-24mm) cenderung memberikan gejala klinis akibat efek massa yang ditimbulkan. Apabila aneurisma terletak di arteri karotis segmen kavernosa, penderita dapat mengalami paresis nervus okulomotor dan juga terkadang memberikan gejala nyeri kepala serta rasa pusing. Pemilihan terapi endovaskuler bergantung pada tipe dan morfologi dari aneurisma. Saat ini, pemilihan terapi endovaskuler dapat berupa stent-assisted coiling dan alat embolisasi pipeline. Kami melaporkan dua kasus aneurisma karotis kavernosa (AKK) tidak pecah berukuran besar simptomatik dengan teknik flow-diverter menggunakan pipeline flex embolization device (PED flex) yang merupakan generasi kedua dari alat embolisasi pipeline. Pada kasus pertama wanita 59 tahun dengan keluhan diplopia dan nyeri kepala, pemeriksaan Computed Tomography (CT) angiografi dan 3 dimensi (D) otak ditemukan aneurisma pada karotis kavernosa bilateral, yang masing-masing berukuran (16,1x16,6mm) pada sisi kanan dan (9,2x6,5mm) pada sisi kiri. Pada kasus kedua, wanita 67 tahun dengan keluhan nyeri kepala. Pemeriksaan MRA otak ditemukan aneurisma berukuran 15mm pada karotis kavernosa sebelah kanan. Masing-masing aneurisma diterapi dengan PED flex (4,75mm diameter/25mm panjang dan 4mm diameter/25mm panjang), kecuali aneurisma pada karotis kavernosa sebelah kiri pada kasus pertama. Follow-up pada enam bulan dan satu tahun kemudian, dengan pemeriksaan angiografi, menunjukkan oklusi komplet pada masing- masing aneurisma. Terapi endovaskular dengan teknik flow-diverter menggunakan PED flex merupakan modalitas terapi yang efektif dan dapat dilaksanakan untuk aneurisma karotis kavernosa berukuran besar bergejala.Kata kunci: Aneurisma karotis kavernosa besar, embolisasi, flow-diverter, pipeline flex embolization device (PED flex)